2016
DOI: 10.1016/j.jccase.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Two adult cases of Bland–White–Garland syndrome with lethal arrhythmia due to coronary steal phenomenon during physical or mental stress

Abstract: IntroductionAnomalous origin of the left coronary artery from the pulmonary artery (ACLAPA) is widely called BWG syndrome, and was first reported by Bland, White, and Garland in 1933 [1]. This is a rare congenital heart disease with prevalence of one in 300,000 births or 0.25-0.5% of all congenital heart disease [2]. The left main coronary artery (LMCA) originates from the main pulmonary artery in more than 90% of cases of BWG syndrome. We herein report two notable adult BWG syndrome cases that presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Over time, myocardial fibrosis and scarring develop because of chronic ischemic changes related to this coronary steal phenomenon, or rerouting of coronary blood flow from high-resistance coronary vessels to low-pressure pulmonary circulation. 7 A few histologic studies have reported higher vascular resistance and greater arteriolar wall thickening in patients with alcapa, which causes the coronary slow flow phenomenon identified during coronary angiography. 8 Adults with alcapa may present with dyspnea, chest pain, palpitations, dysrhythmia, myocardial infarction, cyanosis, syncope, mitral regurgitation, cardiac arrest, or sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, myocardial fibrosis and scarring develop because of chronic ischemic changes related to this coronary steal phenomenon, or rerouting of coronary blood flow from high-resistance coronary vessels to low-pressure pulmonary circulation. 7 A few histologic studies have reported higher vascular resistance and greater arteriolar wall thickening in patients with alcapa, which causes the coronary slow flow phenomenon identified during coronary angiography. 8 Adults with alcapa may present with dyspnea, chest pain, palpitations, dysrhythmia, myocardial infarction, cyanosis, syncope, mitral regurgitation, cardiac arrest, or sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%
“…These adaptations allow perfusion of the LV in a retrograde fashion. Over time, myocardial fibrosis and scarring develop because of chronic ischemic changes related to this coronary steal phenomenon, or rerouting of coronary blood flow from high-resistance coronary vessels to low-pressure pulmonary circulation 7. A few histologic studies have reported higher vascular resistance and greater arteriolar wall thickening in patients with ALCAPA, which causes the coronary slow flow phenomenon identified during coronary angiography 8…”
Section: Discussionmentioning
confidence: 99%
“…A modified-Takeuchi procedure was performed, and an ICD was implanted. The patient's postoperative course was uneventful, and as of 11.5 years after the surgical correction, he is alive and well with no complications and no ICD activations [10)].…”
Section: Casementioning
confidence: 99%